Dalla povertà educativa alla valutazione del successo scolastico: concetti, indicatori e strumenti validati a livello nazionale - Fabio Alivernini; Sara Manganelli; Fabio Lucidi (LED Edizioni Universitarie, 2017)
The article discusses several models for contrasting educational poverty, demonstrating the need for actions aimed at increasing the resilience of disadvantaged children and adolescents. Different types of factors promoting resilience, on which a direct intervention of teachers and educators is possible, are identified. Subsequently, tools for evaluating these resilience factors at the individual as well as at the group-level are presented, describing their theoretical approach, their scope and their psychometric properties. For each presented indicator, the available information about gender differences and immigrant background differences is reported.